Tegillarca granosa shell combination with Vitis vinifera and fluoride in decreasing enamel microporosity - Setiawan, Grace Caroline; Tinisia, Adelia; Rahim, Muhammad Galang Adhinata Abdul; Rahmitasari, Fitria; Prananingrum, Widyasri (Dental Journal (Majalah Kedokteran Gigi), 2024)
Background: White spot lesion is a demineralization process indicated by the increased of enamel microporosity. A tegillarca granosa shell contains 98.7% calcium and Vitis vinifera contains phytochemical compounds with fluoride, which has a potential to stimulate remineralization. Purpose: To analyze the Tegillarca granosa shell combination with Vitis vinifera and fluoride in decreasing enamel microporosity. Methods: The cream was prepared by combining 10% and 20% Tegillarca granosa shell with 10 grams of Vitis vinifera extract and 100 mg of fluoride. The cream was tested beforehand for viscocity and pH. Furthermore, 16 premolars were etched and divided into four groups. Group 1 was smeared with placebo (negative control) and Group 2 was smeared with casein phosphopeptide-amorphous calcium phosphate (positive control). The other groups were smeared with cream 10% (Group 3) and 20% (Group 4) Tegillarca granosa shell combination with Vitis vinifera and fluoride. Teeth were treated three times a day for 30 minutes and soaked in artificial saliva. After 14 days, the enamel microporosity was carried out using a scanning electron microscope. The data was analyzed with one-way analysis of variance (ANOVA) test followed by post-hoc least significant difference (LSD). Results: The enamel microporosity showed significant difference between Group 1 and the other groups. There was no significant difference between Groups 2, 3, and 4 (p<0.05). Although there was no significant difference between Group 3 and 4, the lowest one was in Group 4 (p>0.05). Conclusion: The cream, prepared by combining Tegillarca granosa shell with Vitis vinifera and fluoride, is effective in decreasing the enamel microporosity.